The Impact of Diabetes Mellitus in COVID-19: A Mechanistic Review of Molecular Interactions - Habib Yaribeygi; Thozhukat Sathyapalan; Tannaz Jamialahmadi; Amirhossein Sahebkar (Journal of Diabetes Research)
The ongoing pandemic of COVID-19 is now the major issue in global health. Evidence implies that patients with diabetes are at a higher risk of severe disease or death due to COVID-19 than individuals without diabetes. However, the underlying mechanism for this differential effect in individuals with and without diabetes is not clearly understood. We have reviewed the pathophysiological pathways which may facilitate the entry of virus or an increase in its infectivity in host cells in the diabetic milieu. We suggest that the preexisting pathological pathways in patients with poorly controlled diabetes increase the risk of infectivity and are responsible for the higher levels of tissue injury and death in patients with diabetes.